PENGARUH KEPEMILIKAN EMAS TERHADAP CITRA SOSIAL PEREMPUAN DALAM PERSPEKTIF EKONOMI ISLAM - Nurma Yuritasari (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Gold serves as a dual-function asset for women, acting as both an investment tool (store of value) and a symbol of social status (social signaling). The phenomenon of gold ownership among women is often driven not only by economic motives but also by sociological motives to enhance self-image and recognition within society. This article aims to analyze the influence of gold ownership on the formation of women's social image and review it through the perspective of Islamic economic ethics. The research method used is qualitative with a literature review approach (library research), examining secondary data from scientific journals, textbooks, as well as arguments from the Qur'an and Hadith. The study results indicate that in the view of Islamic economics, gold ownership is permissible as a form of wealth preservation (hifz al-mal). However, it becomes reprehensible when used as a tool for riya (showing off) and tabarruj (excessive adornment) for the sake of social prestige. Islamic economics reconstructs women's social image not based on the quantity of gold displayed, but on the compliance in paying gold zakat as the true social function of wealth.